Cryptoccal meningitis in non-HIV, non-organ transplant diabetic patients - Biradar, Sneha; Teli, Balakrishna (International Journal of Advances in Medicine, 2021)
Cryptococcosis is an important opportunistic fungal infection and also cause of death due to central nervous system disease among patients with human immunodeficiency virus worldwide. Most of the cases occur in immunocompromised patients like HIV infected people, people with organ transplants and on immunosuppressants. Nowdays there is increase in cases of cryptoccal meningitis among diabetic patients. Current case series includes cryptococcal meningitis among diabetic patients after ruling out of other immunocompromised states.